Cell-type preference of immunoglobulin kappa and lambda gene promoters. - Picard, D (1985)
Immunoglobulin gene constant regions are known to be associated with strictly tissue-specific enhancer elements. Until recently the promoter of the variable region, which becomes linked to the constant region by somatic rearrangement, could have been viewed as a passive recipient of the enhancer stimulus. Here we show that the promoters of the immunoglobulin kappa and lambda light chain genes are approximately 20-30 times more active in lymphoid cells than in non-lymphoid cells. To avoid the problem of differential mRNA stability upon transfection of immunoglobulin genes into non-lymphoid cells we have constructed chimeric genes. All kappa mRNA sequences were progressively deleted to fuse the kappa gene promoter to a globin gene coding body. A similar chimeric gene was constructed with the promoter of the lambda gene. The cell-type preference of the promoter may be exploited during B-lymphocyte differentiation to regulate the immunoglobulin gene promoter independently from the enhancer.